Design and Analysis of Lower Limb Assistive Exoskeleton - Keerthana, J.; Harish Krishna, R.; Krishnamoorthy, M.; Hariharan, R.; Kumaresan, R. (Asian Review of Mechanical Engineering, 2022)
Assistive Exoskeleton is a type of ergonomic product that is based on exoskeleton support and is a chair. Standing for five hours or more each day, according to a small study, increases the risk of considerable and prolonged lower-limb muscular fatigue. Long-term back pain and musculoskeletal problems may be increased as a result of this. Meanwhile, the researchers discovered that persons who primarily stand at work are several percent more likely than "predominantly sitting populations" to suffer heart disease. Because of its big size, high weight (5 to 7 kg), and hard frame, the traditional chair is inconvenient to transport to different working locations. As a result, they are unsuited for workplaces with limited space. Because lightweight members are used, the flexible wearable chair may have a gross weight of 3 kg. It has to be constructed in such a way that workers may be comfortable while performing their activities and can adjust their sitting posture to any angle between 90 and 160 degrees. This exoskeleton can be used as an extra pair of legs to allow a person to sit without using a chair or to adopt a more comfortable position for certain occupations. Workers can walk around normally, but they must adjust and secure the supporting structure in the proper position if they want to sit or lean. The weight is then balanced on the floor by their movable frames. It’s designed for factory workers who must stand for extended periods of time in work and occasionally bend into unusual positions to build a product. Spatial management is a critical aspect in every industry. By optimizing the utilization of an Assistive Exoskeleton, superfluous chairs and resting areas can be avoided.